Tank-binding kinase 1 regulates inflammation and autophagy in glaucoma - Morgan, Autumn B.; Inman, Denise M. (Frontiers in Neuroscience, 2026)
TANK-binding kinase (TBK1) copy number variations have been identified as a monogenic cause of familial normal tension glaucoma (NTG). While elevated intraocular pressure (IOP) is a common risk factor in primary open angle glaucoma (POAG), NTG develops in the absence of IOP elevation. The current available standard of care for glaucoma is lowering IOP, highlighting the need to explore alternative therapeutic mechanisms. The established roles of TBK1 in nuclear factor kappa B (NF-κB) and interferon regulatory factor (IRF) signaling, as well as its involvement in autophagy, suggest it may contribute to glaucomatous neurodegeneration by exacerbating retinal ganglion cell (RGC) stress and optic nerve (ON) damage. This review aims to consolidate current knowledge on the contribution of TBK1 to glaucomatous pathology, focusing on its genetic and molecular roles. By identifying gaps in understanding, this work seeks to guide future research efforts into the mechanisms underlying TBK1’s influence on NTG and to explore therapeutic strategies targeting its pathways.